Health-related Quality Of Life Of Adult With Type 2 Diabetes Mellitus In Rural Area - Nur Fadhilah Basir,; Muhamad Hanafiah Juni,; Hejar A.R.,; Ahmad Zaid Fattah Azman,; Dzulkhairi; Zairina A. Rahman (Universiti Putra Malaysia (UPM), 2024)
Introduction: